KEADILAN DISTRIBUTIF DALAM EKONOMI ISLAM - Nurdiansyah, Irdan; Andani, Listia (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2022)
Fair distribution of wealth is a manifestation of justice in Islam. In contrast to the pre-existing distributive justice theory, Islam regulates justice in a comprehensive way. The writing is processed using the literature study method obtained from various books, journals, and other related references. Distributive justice in the Islamic perspective is not related to the benefits that will be obtained in this world, but also in the hereafter. Islam demands maximizing benefit for the common good and minimizing harm. The concept offered by Islam is able to be a balancer as well as a solution for equality and justice in a social order.Â